Clonal dissemination of carbapenem-resistant Klebsiella pneumoniae ST16 co-producing NDM-1 and OXA-232 in Thailand. Issue 4 (16th August 2022) - Abe, Ryuichiro; Akeda, Yukihiro; Takeuchi, Dan; Sakamoto, Noriko; Sugawara, Yo; Yamamoto, Norihisa; Kerdsin, Anusak; Matsumoto, Yuki; Motooka, Daisuke; Leolerd, Warawut; Santanirand, Pitak; Suzuki, Masato; et al.
Abstract: Background: Klebsiella pneumoniae ST258 and ST11 carrying bla KPC are among the most widespread carbapenem-resistant K. pneumoniae strains worldwide. Our carbapenem-resistant Enterobacteriaceae surveillance in Thailand revealed a nationwide dissemination of K. pneumoniae ST16 isolates carrying bla NDM-1 and bla OXA-232 . Objectives: To analyse the genomic details of this nationwide dissemination by focusing on plasmids and virulence factors. Methods: Using WGS data of 119 K. pneumoniae ST16 isolates carrying bla NDM-1 obtained in our previous surveillance study, clonality of chromosomes and plasmids of the isolates with carriage of virulence factors was evaluated. Results: Of the 119 isolates, 111 carried plasmid pKP151_NDM1, and all 104 isolates harbouring bla OXA-232 carried plasmid pKP151_OXA232. These 104 K. pneumoniae ST16 isolates showing chromosomal clonality possessed both pKP151_NDM1 and pKP151_OXA232, demonstrating clonal dissemination of K. pneumoniae ST16 with these plasmids. The isolates had essentially similar virulence factors as those of K. pneumoniae ST16 clones carrying bla KPC, which were recently reported as highly invasive clones in Brazil. Conclusions: The potential global dissemination of these invasive clones with resistance to several antibiotics highlights the importance of appropriate monitoring and strict standard precautions.